Audit at the request of a member of a business entity: issues of legal identification and law enforcement - E. A. Bochkareva (Гуманитарные и юридические исследования)
Introduction. Participants in partnerships and societies often face problems in exercising the right to information in the form of an audit, resorting to judicial protection after exhausting pre-trial settlement methods. The article offers a justification for the requested inspection as mandatory. It is argued that in the context of updating the legislation on auditing activities, there is an expansion of the range of issues to be clarified by the courts when considering disputes regarding the exercise of the right to conduct an audit.Materials and methods. The study is based on the analysis of arbitration court decisions on disputes in the area of exercising the right to conduct an audit of a business company by its participants. The legal identification of an audit at the request of a participant in a business company as mandatory was carried out using the method of analogy and the formal legal method.Analysis. The grounds for conducting an audit of a business company by its participants are established by a norm of federal law, imperative according to the method of legal regulation, and the content of the emerging legal relations is characterized by the requirement to conduct an audit and the obligation to conduct it corresponding to each other. While not being de jure mandatory, the audit in question is de facto mandatory. Examining the circumstances of disputes regarding the exercise of the right to conduct an audit, the court consistently determines: firstly, whether the plaintiff has the status of a participant in the company; secondly, whether he submitted a corresponding demand to the company, and with what result; thirdly, the court should make sure that a company participant has no signs of abuse of the right to receive information about the activities of the company. The court also evaluates the parties’ compliance with the requirements of the legislation on auditing activities and their fulfillment of responsibilities related to the audit.Results. An audit at the request of participants in partnerships and companies corresponds to the characteristics of a mandatory audit. Clause 2 of Article 5 of the Federal Law “On Auditing Activities” needs clarification, which establishes the annuality of mandatory audits by including in it other cases provided for by federal laws. It has been established that when considering disputes regarding the audit of a business company, the courts are guided by the approaches formulated in the documents of the Presidium of the Supreme Arbitration Court of the Russian Federation on the provision of information to participants of business companies. At the same time, in the context of updating legislation on auditing activities, courts will need to pay attention to compliance with the rules of independence of auditors and audit organizations, as well as evaluate the audit agreement for the presence of information in it about the new subject of audit legal relations - the head of the audit.